Evaluasi Resistensi Progeni Anggrek Phalaenopsis terhadap Penyakit Busuk Lunak (Pseudomonas viridiflava) - Hanudin Hanudin; Indijarto Budi Rahardjo; Kurniawan Budiarto (Jurnal Fitopatologi Indonesia, 2017)
A bacterial soft rot disease caused by P. viridiflava was one of problems in orchid nursery, especially Phalaenopsis.  An evaluation on progenies derived from three crossing combinations were conducted to find out the symptom characteristic, development of infections of the disease and resistance response of the progenies against artificial infection of P. viridiflava. The research was conducted under a standard glass house conditions for Phalaenopsis involving 31 individuals from 3 progeny populations, namely P.157, E.2153 and E.2189. The results showed that symptoms were characterized by the lesion of the leaf tissues. On most accessions, the lesion enlarged and foul odor was detected as an indication of the successful establishment of bacterial infection. Based on the disease severity, three accessions (P.157-12, P.157-45, and P.157-71) had the lowest infections and were classified into resistant genotypes. One accession, i.e. P.157-32 was classified as susceptible and the rest 27 accessions were grouped into very susceptible class.